CAUSES AND PREVENTION OF DIABETIC POLYNEUROPATHY. - Amonova Zakhro Kakhramonovna; Akmaljon Akhmatjonovich Gaybiyev; Amonova Zilola Kahramonovna (TADQIQOTLAR.UZ, 2024)
Abstract: Diabetic polyneuropathy is a common complication of diabetes that affects the nerves, especially in the feet and legs. It is caused by prolonged exposure to high levels of glucose in the blood, which can damage nerves over time. The exact mechanism by which high blood sugar causes nerve damage is not fully understood, but it is believed to involve a combination of metabolic, vascular, and inflammatory factors.